The 12th Symposium on Polar Science, Program and Abstracts, Session IW - 冨川, 喜弘; 江尻, 省; 西山, 尚典; Tomikawa, Yoshihiro; Ejiri, Mitsumu K.; Nishiyama, Takanori (2021)
The 12th Symposium on Polar Science, 15–18 Nov. 2021, National Institute of Polar Research (NIPR) Research Organization of Information and Systems (ROIS) conference object